System of actions to prepare teachers for the creation of open educational resources - Consuegra, Maida Librada Bilbao; Gómez, Nancy Andreu (Advanced Notes in Information Science, 2024)
The Ministry of Higher Education has made the creation of massive open online courses (MOOCs) in universities as a key objective in part of the digital transformation of Cuban universities. This has led to a need to prepare teachers and managers to face open education. Open educational resources (OER) promote the opening and democratization of knowledge and expand the opportunities for access to information. It is necessary for higher education centers to develop and manage resources to support the teaching–learning process and to prepare their teachers in the production of these resources. The objective of this paper is to present the results of the Virtual Learning and Distance Education Group of the Universidad Central “Marta Abreu” de Las Villas in the work with the preparation of teachers to face open education. Specifically, the paper will focus on the actions taken to prepare teachers for the creation of OER. The results shown were obtained using the systematization of experiences as an essential method of qualitative research. A comprehensive system of strategic actions has been developed and implemented across various domains, with the objective of preparing teachers to engage with open education, particularly as creators of OER. Work stages have been delineated to facilitate the transition to open education and the development of OER by teachers.